2015
DOI: 10.2169/internalmedicine.54.3927
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Steroid Therapy in Adult Minimal Change Nephrotic Syndrome: A Systematic Review and Meta-analysis

Abstract: The best regimen for adult minimal change nephrotic syndrome (MCNS) is still unknown. Due to an excessive number of adverse events caused by oral steroid monotherapy, enhanced steroid therapy (low dose of prednisolone with a short course of methylprednisolone or with another immunosuppressant) has been studied extensively for years. In this study, the PubMed, Embase, EBSCO and Cochrane Library databases were searched for clinical trials which compared enhanced steroid therapy with oral steroid monotherapy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Consequently, most clinicians recommend treatment for minimal change disease patients with high doses of corticosteroids. However, this is a rare disease and there is a paucity of data from randomized controlled trials in adults on the efficacy of therapy [10][11][12] . Many adult patients require a prolonged initial course of corticosteroids to enter remission 9,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most clinicians recommend treatment for minimal change disease patients with high doses of corticosteroids. However, this is a rare disease and there is a paucity of data from randomized controlled trials in adults on the efficacy of therapy [10][11][12] . Many adult patients require a prolonged initial course of corticosteroids to enter remission 9,[13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…MCD is generally a steroid-sensitive disease; however, the rate of response of MCD to corticosteroid therapy is lower in adults compared with children, and more prolonged therapy is required to achieve a remission [17]. A systematic review of the treatment of MCD concluded that patients treated with steroid pulse therapy achieved complete remission sooner and showed fewer adverse events than did patients receiving oral steroid monotherapy [18], but complete remission rates and relapse rates were similar in both groups. Steroid pulse therapy was not performed in the previously reported 4 cases of de novo MCD during pregnancy; however, steroid pulse therapy should be particularly considered for pregnant women with nephrotic syndrome, for whom acute kidney injury threatens.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, relapse is very common in these patients and then high-dose or long-term steroid therapy is often recommended. However, repeated and prolonged steroid therapy is associated with an excess of adverse events, some of which are dose related (Zhao et al, 2015a). Previous studies confirmed that US combined with MBs could enhance the delivery of genes or drug to target areas of tissues including the kidney (Ibsen et al, 2013;Aryal et al, 2014;Huang et al, 2016;Wei et al, 2016).…”
Section: Downloaded Frommentioning
confidence: 99%